2016
DOI: 10.1161/circresaha.115.308278
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Renal Denervation Protects the Ischemic Heart via Inhibition of GRK2 and Increased Nitric Oxide Signaling

Abstract: Rationale:Catheter-based renal denervation (RDN) is currently under development for the treatment of resistant hypertension and is thought to reduce blood pressure via interruption of sympathetic pathways that modulate cardiovascular function. The sympathetic nervous system also plays a critical role in the pathogenesis of acute myocardial infarction and heart failure.Objective:We examined whether treatment with radiofrequency (RF)-RDN would protect the heart against subsequent myocardial ischemia/reperfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 53 publications
5
27
0
Order By: Relevance
“…Recently, catheter-based RD to treat patients with CKD was shown to inhibit sympathoexcitatory reflexes, and the interruption of these afferent reflexes led to a reduction in systemic sympathetic tone6. Other potential effects of RD have been reported, including improvements in LVH3435, an antiarrhythmic effect including atrial fibrillation36, and myocardial reperfusion injury37. Our study further showed that RD ameliorated the baroreflex and partially improved the renal function and LVH.…”
Section: Discussionsupporting
confidence: 66%
“…Recently, catheter-based RD to treat patients with CKD was shown to inhibit sympathoexcitatory reflexes, and the interruption of these afferent reflexes led to a reduction in systemic sympathetic tone6. Other potential effects of RD have been reported, including improvements in LVH3435, an antiarrhythmic effect including atrial fibrillation36, and myocardial reperfusion injury37. Our study further showed that RD ameliorated the baroreflex and partially improved the renal function and LVH.…”
Section: Discussionsupporting
confidence: 66%
“…Nitrite content of plasma and myocardial specimens was made using an ENO‐30 ion chromatography system with a PC‐PAK precolumn and an NO‐PAK separation column (Eicom), as previously described . The mobile phase was composed of 10% methanol with 0.15 mol/L NaCl‐NH 4 Cl and 0.5 g/L tetrasodium EDTA supplied at a flow of 0.33 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…This alternative strategy is not drug based but could, in fact, replace or supplement current therapies. The first half of this work was published in Circulation Research in 2016 4,5 ; we're finalizing the second half now and plan to submit it soon for publication.…”
Section: -3mentioning
confidence: 99%